AdaptNow: a revamped look for the web: an online web enhancement tool for the elderly - Dias, Roberto (2019)
Elderly population will become the largest age group of our society in the next twenty years. Consequently, we need to be able to accommodate technologies to the needs of this population. AdaptNow is a web-based application that allows users to adapt existing webpages and turn them more accessible and user friendly. Users can do so directly from any web browser thanks to AdaptNow's user personalization and automatic adaptation artificial intelligence algorithms. In this paper we present the design and implementation of AdaptNow, a solution that improves navigation on the web for elderly users.